UJI EFEK EKSTRAK ETANOL KULIT TERUNG UNGGU (Solanum melongena L.) TERHADAP KADAR GULA DARAH PADA TIKUS PUTIH JANTAN GALUR WISTAR (Rattus norvegicus) - Aer, Brenda Natalia (PHARMACON, 2013)
This study aimed to determine the effect of ethanol extract eggplant rind (SolanummelongenaL.) on blood sugar levels in white male wistar induced by sucrose. Extraction is done bymaceration with 95% ethanol. The subject of the experiment were 15 white male wistarwhich were divided into 3 (three) groups namely positive control group using metformin 9mg/Kg body weight, negative control group using CMC 1% and treatment group with thedose of 0,02 g/200 g body weight, 0,01 g/200 g body weight and 0,1 g/200 g body weight.The data is processed using ANOVA and LSD test to compare between the positive controlgroup, negative control group, and treatment group. The analysis revealed a significantdifference between negative control group and treatment group, negative control group andpositive control group, but did not show a significant difference between positive controlgroup and treatment group.Key words : Solanummelongena L., Eggplant Rind, Blood Sugar Level, Sucrose